Pituitary Volume in Individuals with Social Anxiety Disorder - Koc, Mustafa; Mermi, Osman; Aslan, Sabriye; Atmaca, Murad (Aves, 2022)
Background: There are no volumetric magnetic resonance imaging studies on the pituitary gland in individuals with social anxiety disorder. The present study aimed to investigate pituitary volume in individuals with social anxiety disorder compared to healthy controls due to the correlation between pituitary gland volume and stress response and the hypothalamic-pituitary-adrenal axis and hypothesized that pituitary gland volume would be different in these individuals. Methods: In this study, 21 individuals with social anxiety disorder based on fourth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) and 20 healthy controls were included. Both patient and control groups were scanned with a 1.5-Testa General Electric (GE) Magnetic Resonance Imaging scanner. Pituitary volume was measured with the manual tracing method. Results: The statistical analysis revealed that the mean pituitary gland volume of the individuals with social anxiety disorder was significantly smaller when compared to that of healthy controls, statistically, as presented in Table 1 [594.10 +/- 104.56 mm(3) for individuals with social anxiety disorder and 818.01 +/- 215.25 mm(3) for healthy controls] when it was done by using the analysis of covariance controlled for age (F=12.979, df=1, P < .001), sex (F=11.448, df=1, P < .001), and total brain volume (F=10.772, df=1, P < .001), demonstrating that smaller pituitary volume in social anxiety disorder, when compared to healthy subjects, was an important finding independent of age, sex, or total brain volume. Conclusion: We suggest that social anxiety disorder may be associated with smaller pituitary volume, supporting the notion that anxiety itself could reduce the pituitary volume.
Keywords: HPA; MRI; pituitary; social anxiety disorder; volume